Design of a pedestrian bridge on the displaced riverbed of the Ćehotina River in Pljevlja, Montenegro - Jovanović Nikola; Stefanović Jelena; Živanović Miloš; Pavlović Zlatko; Miljković Nikola (Mining and Metallurgy Engineering Bor)
This paper aims to review the design of a pedestrian bridge on the displaced riverbed of the Ćehotina River in city Pljevlja. The footbridge is intended for pedestrian and cyclist traffic. The design of the pedestrian bridge is part of the Main Design of Bridges on the Displaced Riverbed of the Ćehotina River. The paper describes in detail the bridge design, the choice of a static calculation software, as well as which standards were used for dimensioning the elements and adopting legally prescribed bridge dimensions.